LOS DERECHOS HUMANOS Y EL MEDIO AMBIENTE EN COLOMBIA EN LOS INICIOS DEL SIGLO XXI (2019)
This article refers to the permanent violation of individual and collective human rights; to the permanent violation of the environment, by social actors, who profit from the benefits of nature, ignoring the consequences of the irresponsible practice of the excessive exploitation of illegal mining, illicit crops, pollution of water sources, the excessive exploitation of illegal mining, the environmental damage of forests and forests that are the source of water production from where a large part of the population is kept and that today, with the complicity of some of the institutions, not only violate the rights human beings, but they threaten the environment of our country and contribute irresponsibly to more critical problems such as global warming and climate change.